A compound and its use, lithium cobalt oxide positive electrode material and its preparation method, lithium cobalt oxide battery
By secondary coating on the surface of lithium cobalt oxide positive electrode material and coupling specific compounds with lithium cobalt oxide positive electrode material, the shortcomings of lithium cobalt oxide positive electrode material in high temperature and rate resistance are solved, and significantly improved electrochemical performance is achieved.
Patent Information
- Application Number
- CN202411599657.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-11
AI Technical Summary
How to improve the electrochemical performance of lithium cobalt oxide positive electrode materials, especially in terms of high temperature and rate resistance.
By performing secondary coating on the surface of the lithium cobalt oxide positive electrode material that has been coated once, a specific compound is used, with the general formula of R1-C1-4 alkyl and R2-halogen, wherein R1 is at least one of methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, and isopropyl, and R2 is at least one of fluorochloro-bromoiodine. The compound is prepared by condensation reaction and is coupled with the lithium cobalt oxide positive electrode material to form a chelate, which is closely bound and uniformly distributed.
It improves the high temperature resistance and rate performance of lithium cobalt oxide positive electrode material, reduces electrolyte corrosion and surface side reactions, and significantly improves electrochemical performance.
Smart Images

Figure QLYQS_1 
Figure QLYQS_2 
Figure QLYQS_3
Abstract
Description
Technical Field
[0001] The present application relates to the field of lithium cobalt oxide batteries, and in particular to a compound and its use, a lithium cobalt oxide positive electrode material and its preparation method. Background Art
[0002] Lithium-ion batteries (LIBs) are one of the most promising new generation energy storage technologies. They have the advantages of large specific capacity, high voltage, high power, high efficiency and low environmental pollution. Lithium-ion batteries are mainly composed of key components such as positive electrodes, negative electrodes, electrolytes and separators. The electrochemical performance of lithium-ion batteries depends largely on the active materials of the electrodes. Among them, the positive electrode material plays an important role in determining the performance of lithium-ion batteries (such as capacity, thermal stability and potential). It is the main lithium ion (Li) donor in the system, determines the capacity of lithium-ion batteries, and affects the cost of batteries. At present, the common positive electrode materials of lithium-ion batteries mainly include lithium cobalt oxide LiCoO2, lithium manganese oxide, lithium iron phosphate and ternary materials. Among them, lithium cobalt oxide LiCoO2 is still the most widely used and the most mature technology.
[0003] Prior art 1: Chinese patent application 202310521568.7 discloses a composite lithium-rich material and its preparation method, a positive electrode and a secondary battery. The preparation method is: providing a ligand, a lithium-rich material and an organic solvent; mixing the ligand, the lithium-rich material and the organic solvent to obtain a lithium mixed solution; removing the organic solvent from the lithium mixed solution to obtain a composite lithium-rich material; wherein the ligand includes an organic chelating agent.
[0004] This solution uses a composite lithium-rich material as a lithium supplement additive. The lithium ions in the lithium-rich material effectively replenish the lithium ions consumed in the formation process of the SEI film of the lithium-ion battery. At the same time, the organic chelating agent in the ligand effectively chelates the transition metals released by the positive electrode material during the cycle of the lithium-ion battery, avoiding the damage of the SEI film by the transition metal, reducing the lithium ions consumed in the repair of the SEI film, increasing the first charge capacity of the lithium-ion battery, reducing the capacity attenuation during the cycle, and increasing the life of the lithium-ion battery.
[0005] Prior art 2: Chinese patent application 201811384770.5 discloses a lithium battery electrode sheet and a preparation method thereof, wherein the preparation method comprises: dispersing active materials, conductive agents, binders, and chelating agents in a solvent in proportion to prepare battery slurry, coating the slurry on a current collector, and obtaining an electrode sheet through heat treatment and rolling treatment.
[0006] In this scheme, the chelating agent in the slurry has functional groups such as carboxyl and amino, which can interact with the carboxyl or hydroxyl functional groups on the surface of the binder and the active material. At the same time, the chelating agent can also have a strong complexation with the metal surface of the foil (residual metal ions), playing the role of an adhesive. Therefore, the amount of the electrode polymer binder can be reduced while greatly improving the bonding force between the electrode slurry and the current collector foil, thereby improving the battery's cycle life and rate performance while improving the battery's energy density.
[0007] The problem that this solution needs to solve is: How to propose a compound to coat the lithium cobalt oxide positive electrode material to improve the electrochemical performance of the lithium cobalt oxide positive electrode material. Summary of the invention
[0008] The purpose of this application is to propose a compound and a preparation method thereof, a lithium cobalt oxide positive electrode material and a preparation method thereof, and a lithium cobalt oxide battery, and to perform a secondary coating with a compound on the surface of a lithium cobalt oxide positive electrode material that has been coated once, so as to further improve the electrochemical performance of the lithium cobalt oxide positive electrode material.
[0009] To achieve the above purpose, the present application discloses a compound, the general structural formula of the compound is shown in Formula I:
[0010] Formula I;
[0011] Where R1 is C 1-4 alkyl;
[0012] R2 is halogen.
[0013] Preferably, R1 is at least one of methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, and isopropyl;
[0014] The halogen is at least one of fluorine, chlorine, bromine and iodine;
[0015] More preferably, the R1 is isopropyl and the halogen is bromine.
[0016] In addition, the invention also discloses the use of the compound as a coating agent for a lithium cobalt oxide positive electrode material.
[0017] In addition, a preparation method for preparing the above compound is also disclosed, comprising the following steps: 1-4 Compound A containing an alkyl group and a halogen group is subjected to a condensation reaction with glyoxal to obtain compound B, and compound B is then subjected to a condensation reaction with polyoxymethylene and hydrogen chloride to obtain compound B.
[0018] Preferably, it specifically includes:
[0019] Step A: Add compound A, catalyst, 40% glyoxal aqueous solution, and deionized water into a reaction kettle, and slowly add a pH adjuster at a speed of 300 rpm / min, stir for 1 to 3 hours, then add 170 to 210 ml of deionized water, filter, wash with alcohol, and dry to obtain compound B;
[0020] Step B: prepare a 4 mol / L hydrogen chloride dioxane solution, add it together with paraformaldehyde into a reaction kettle, stir at 300 r / min for 25 to 45 min, add compound B and tetrahydrofuran, stir for another 1.8 to 2.2 h, and filter under reduced pressure to obtain a solid powder;
[0021] Step C: dissolve the solid powder in dichloromethane, add ether for precipitation, and filter to obtain the compound.
[0022] The general structural formulas of compound A and compound B are shown in formula II and formula III:
[0023] Formula II;
[0024] Formula III.
[0025] Preferably, in step A, the molar ratio of compound A, catalyst, glyoxal, pH regulator and water is 1:100-112:0.9-1.2:0.05-0.07:40-50;
[0026] In the step B, the molar ratio of paraformaldehyde, hydrogen chloride, compound B and tetrahydrofuran is 1:1.15-1.20:0.39-0.46:9-11;
[0027] In the step C, the mass ratio of dichloromethane to solid powder is 6.61-13.2:1, and the mass ratio of ether to solid powder is 18.4-22.1:1.
[0028] More preferably, the catalyst is n-propanol, and the pH adjuster is formic acid.
[0029] In addition, a lithium cobalt oxide positive electrode material is also disclosed, comprising a lithium cobalt oxide core layer and the above compound coated on the surface of the lithium cobalt oxide core layer.
[0030] In addition, a preparation method for preparing the above-mentioned lithium cobalt oxide positive electrode material is also disclosed, and the compound is coated on the surface of the lithium cobalt oxide core layer.
[0031] Preferably, the method comprises the following steps:
[0032] Step 1: Mixing and sintering a lithium source and a cobalt source to prepare a sintered material;
[0033] Step 2: Mix the compound and the calcined material and heat and keep the mixture to obtain a lithium cobalt oxide positive electrode material.
[0034] More preferably, the method specifically comprises the following steps:
[0035] Step 1: Mixing a cobalt source, a lithium source, and a metal oxide containing element D to obtain a mixed material;
[0036] Step 2: placing the mixed material in an air atmosphere, and performing one-time sintering, jaw crushing, rolling, crushing, screening and demagnetization operations to obtain a primary sintered material;
[0037] Step 3: Mix the primary sintered material with the coating E and the metal oxide containing the element D, place in an air atmosphere for secondary sintering, crushing, sieving, and demagnetization to obtain a secondary sintered material;
[0038] Step 4: After mixing the secondary sintered material with the compound, heating and maintaining the temperature, a lithium cobalt oxide positive electrode material is obtained.
[0039] Preferably, the element D is selected from at least one of Mg, Al and Ti:
[0040] The coating E is selected from at least one of Co(OH)2 and CoOOH;
[0041] In step 3, the amount of coating E added is 1-2% of the mass of the primary sintering material, and the amount of metal oxide containing element D added is 0.1-0.3% of the mass of the primary sintering material;
[0042] The added amount of the compound in step 4 is 0.06% to 0.16% of the mass of the secondary sintered body.
[0043] In addition, a lithium cobalt oxide battery is also disclosed, which contains the lithium cobalt oxide positive electrode material.
[0044] The beneficial effects of this application are:
[0045] The present application provides a compound and its use, a lithium cobalt oxide positive electrode material and its preparation method, and a lithium cobalt oxide battery, which utilizes the good thermal stability of the compound to improve the high temperature resistance of the material; and the compound has a certain conductivity, which improves the rate performance of the material. At the same time, the compound and the first coating layer form a chelate through coupling, which is tightly combined and evenly distributed on the first coating layer, which can effectively hinder electrolyte corrosion, reduce surface side reactions, and further improve the electrochemical performance of the lithium cobalt oxide positive electrode material. DETAILED DESCRIPTION
[0046] In the description of this application, it should be noted that if the specific conditions are not specified in the examples, the experiments were carried out according to conventional conditions or the conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not specified, are all conventional products that can be purchased commercially.
[0047] Example 1
[0048] The preparation method of the compound is:
[0049] Step A: Compound A, n-propanol, 40% glyoxal aqueous solution, and deionized water were added into a reaction kettle, and the molar ratio of compound A, n-propanol, polyoxymethylene and water was 1:106:10.5:45, and formic acid was slowly added at a speed of 300 rpm / min, stirred for 2 hours, and then 200 ml of deionized water was added, filtered, washed with methanol, and dried to obtain compound B;
[0050] Step B: prepare a 4 mol / L hydrogen chloride dioxane solution, add it together with paraformaldehyde into a reaction kettle, stir at 300 r / min for 35 min, add compound B and tetrahydrofuran, wherein the molar ratio of paraformaldehyde, hydrogen chloride, compound B and tetrahydrofuran is 1:1.17:0.43:10, stir for another 2.0 h, filter under reduced pressure to obtain a solid powder;
[0051] Step C: dissolving the solid powder in dichloromethane with a mass of the solid powder, adding ether for precipitation, and filtering to obtain a compound. The mass ratio of dichloromethane to solid powder is 7.3:1, and the mass ratio of ether to solid powder is 19.8:1;
[0052] Wherein, the compound A is 4-bromo-2,6-diisopropylaniline (CAS: 1447939-74-3);
[0053] Compound B is N1,N2-bis(4-bromo-2,6-diisopropylaniline)ethane-1,2-diimine;
[0054] The compound structural formula is shown in Formula IV:
[0055] Formula IV.
[0056] The preparation method of lithium cobalt oxide positive electrode material is as follows:
[0057] Step 1: mixing cobalt tetroxide, lithium carbonate, and MgO in a mass ratio of 1:1.03:0.02 to obtain a mixed material;
[0058] Step 2: Place the mixed material in an air atmosphere, heat it to 700℃ and sinter it for 2h, then heat it to 1000℃ and sinter it for 7h, complete the primary sintering, jaw crusher, roller, crushing, 350 mesh sieving and demagnetization operations to obtain the primary sintering material;
[0059] Step 3: Mix the primary sintered material, Co(OH)2 added in an amount of 1.5% of the mass of the primary sintered material, and MgO added in an amount of 0.2% of the mass of the primary sintered material, heat it to 925°C in an air atmosphere, and sinter it for 10 hours to complete the secondary sintering, crush it, sieve it through 350 mesh, and demagnetize it to obtain the secondary sintered material;
[0060] Step 4: After mixing the secondary sintered material with a compound added in an amount of 0.11% of the mass of the secondary sintered material, the temperature was raised to 100° C. and kept warm for 1.3 hours to obtain a lithium cobalt oxide positive electrode material.
[0061] Example 2
[0062] The method is basically the same as Example 1, except that the preparation method of the lithium cobalt oxide positive electrode material is:
[0063] Step 1: mixing cobalt tetroxide, lithium carbonate, and MgO in a mass ratio of 1:1.02:0.03 to obtain a mixed material;
[0064] Step 2: Place the mixed material in an air atmosphere, heat it to 700℃ and sinter it for 2h, then heat it to 1000℃ and sinter it for 7h, complete the primary sintering, jaw crusher, roller, crushing, 350 mesh sieving and demagnetization operations to obtain the primary sintering material;
[0065] Step 3: Mix the primary sintered material, Co(OH)2 added in an amount of 1% of the mass of the primary sintered material, and MgO added in an amount of 0.1% of the mass of the primary sintered material, place it in an air atmosphere, heat it to 925°C, and sinter it for 10 hours to complete the secondary sintering, crush it, sieve it through 350 mesh, and demagnetize it to obtain the secondary sintered material;
[0066] Step 4: After mixing the secondary sintered material with a compound added in an amount of 0.06% of the mass of the secondary sintered material, the temperature was raised to 100° C. and kept warm for 1.3 hours to obtain a lithium cobalt oxide positive electrode material.
[0067] Example 3
[0068] The method is basically the same as Example 1, except that the preparation method of the lithium cobalt oxide positive electrode material is:
[0069] Step 1: mixing cobalt tetroxide, lithium carbonate, and MgO in a mass ratio of 1:1.05:0.01 to obtain a mixed material;
[0070] Step 2: Place the mixed material in an air atmosphere, heat it to 700℃ and sinter it for 2h, then heat it to 1000℃ and sinter it for 7h, complete the primary sintering, jaw crusher, roller, crushing, 350 mesh sieving and demagnetization operations to obtain the primary sintering material;
[0071] Step 3: Mix the primary sintered material, Co(OH)2 added in an amount of 2% of the mass of the primary sintered material, and MgO added in an amount of 0.3% of the mass of the primary sintered material, place it in an air atmosphere, heat it to 925°C, and sinter it for 10 hours to complete the secondary sintering, crush it, sieve it through 350 mesh, and demagnetize it to obtain the secondary sintered material;
[0072] Step 4: After mixing the secondary sintered material with a compound added in an amount of 0.16% of the mass of the secondary sintered material, the temperature was raised to 100° C. and kept warm for 1.3 h to obtain a lithium cobalt oxide positive electrode material.
[0073] Example 4
[0074] It is basically the same as Example 1, except that, in the compound, compound A, and compound B, the R1 group is an isopropyl group, and the R2 group is an F group.
[0075] Example 5
[0076] It is basically the same as Example 1, except that, in the compound, compound A, and compound B, the R1 group is an isopropyl group, and the R2 group is a Cl group.
[0077] Example 6
[0078] It is basically the same as Example 1, except that, in the compound, compound A, and compound B, the R1 group is a methyl group, and the R2 group is a Br group.
[0079] Example 7
[0080] It is basically the same as Example 1, except that, in the compound, compound A, and compound B, the R1 group is an ethyl group, and the R2 group is a Br group.
[0081] Example 8
[0082] It is basically the same as Example 1, except that, in the compound, compound A, and compound B, the R1 group is a tert-butyl group, and the R2 group is a Br group.
[0083] Example 9
[0084] It is basically the same as Example 1, except that the metal oxide containing element D in step 1 and step 3 is Al2O3.
[0085] Example 10
[0086] It is basically the same as Example 1, except that the metal oxide containing element D in step 1 and step 3 is TiO2.
[0087] Embodiment 11
[0088] It is basically the same as Example 1, except that the primary sintering process is: first heating to 600° C. and keeping warm for 3 hours; then heating to 950° C. and keeping warm for 10 hours.
[0089] Example 12
[0090] It is basically the same as Example 1, except that the primary sintering process is: first heating to 800° C. and keeping warm for 1 hour; then heating to 1050° C. and keeping warm for 5 hours.
[0091] Embodiment 13
[0092] It is basically the same as Example 1, except that the secondary sintering temperature is 900° C. and the holding time is 12 h.
[0093] Embodiment 14
[0094] It is basically the same as Example 1, except that the secondary sintering temperature is 950° C. and the holding time is 8 hours.
[0095] Embodiment 15
[0096] The method is basically the same as Example 1, except that the insulation temperature in step 4 is 80° C. and the insulation time is 1.7 h.
[0097] Example 16
[0098] It is basically the same as Example 1, except that the insulation temperature in step 4 is 110° C. and the insulation time is 0.8 h.
[0099] Embodiment 17
[0100] It is basically the same as Example 1, except that the coating E in step 3 is CoOOH.
[0101] Embodiment 18
[0102] The method is basically the same as Example 1, except that the insulation temperature in step 4 is 70°C.
[0103] Embodiment 19
[0104] The method is basically the same as Example 1, except that the insulation temperature in step 4 is 120°C.
[0105] Embodiment 20
[0106] It is basically the same as Example 1, except that no coating E is added in step 3.
[0107] Embodiment 21
[0108] The method is basically the same as Example 1, except that the coating E in step 3 is cobalt iodide (CAS: 15238-00-3).
[0109] Embodiment 22
[0110] The method is basically the same as Example 1, except that the metal oxide containing element D is not added in step 1 and step 3.
[0111] Embodiment 23
[0112] The method is basically the same as Example 1, except that zirconium oxide is used to replace MgO in step 1 and step 3.
[0113] Comparative Example 1
[0114] The method is substantially the same as Example 1, except that 1,3-bis(4-bromo-2,6-diisopropyl)-1H-imidazol-3-ium chloride is not used for coating.
[0115] Comparative Example 2
[0116] The method is substantially the same as Example 1, except that Compound 1 (1,3-bis(2,6-diisopropylphenyl)-1H-imidazole-3-chloride, CAS: 1228185-09-8) is used instead of the compound for coating.
[0117] The structural formula of compound 1 is shown in Formula V
[0118] Formula V.
[0119] Comparative Example 3
[0120] The method is basically the same as Example 1, except that Compound A without R1 group is used to prepare Compound 2 (CAS: 1621307-01-4) by the preparation method of the reference compound, which is used instead of the compound for coating.
[0121] The structural formula of compound 2 is shown in Formula VI:
[0122] Formula VI.
[0123] Comparative Example 4
[0124] The method is basically the same as Example 1, except that 1,3-di(isopropylimidazole) chloride (CAS: 157197-54-1) and bromobenzene (CAS: 108-86-1) are mixed in a molar ratio of 1:2 and used instead of the compound for coating.
[0125] Performance Testing:
[0126] Preparation of button-type half-cells: 1. Preparation and performance testing of button-type half-cells: (1) The specific operation of the preparation method of button-type half-cells is as follows: the active positive electrode materials, PVDF and carbon black prepared in the embodiment and the comparative example are mixed in a mass ratio of 94:3:3, and a proper amount of NMP is added and stirred to form a battery slurry. Subsequently, the slurry is evenly coated on an aluminum foil and placed in an oven at 120°C for 3-10 hours. After drying, the positive electrode sheets are cut into uniform sizes, and the loading amount of active substances on the electrode sheets is 8-20 mg / cm 2 The prepared positive electrode sheet was placed in a vacuum glove box, and a metal lithium sheet was used as the negative electrode, and assembled with a separator, an electrolyte and other components into a button-type half-cell.
[0127] Discharge capacity: After the battery is assembled, place the battery on a battery tester (Xinwei integrated electric cabinet) for electrical performance testing. The test environment is a constant temperature of 25°C, the charge cut-off voltage and the discharge cut-off voltage are 4.5V and 3.0V respectively, and the test is obtained by charging to the charge cut-off voltage at a rate of 0.1C and then discharging to the discharge cut-off voltage.
[0128] First discharge efficiency: After the above discharge capacity test is completed, it can be obtained by dividing the actual discharge capacity by the charge capacity.
[0129] 4C discharge capacity retention rate: After the battery is assembled, place the battery on a battery tester (Xinwei integrated electric cabinet) for electrical performance testing. The test environment conditions are a constant room temperature of 25°C, the charge cut-off voltage and the discharge cut-off voltage are 4.5V and 3.0V respectively, and the test data are divided by the test data of charging to the charge cut-off voltage and then discharging to the discharge cut-off voltage at 0.1C and 4C rates.
[0130] Capacity retention rate of 80-week cycle at 1C at room temperature: After the battery is assembled, the battery is placed on a battery tester (Xinwei integrated electric cabinet) for electrical performance testing. The test environment conditions are a constant room temperature of 25°C, the charge cut-off voltage and the discharge cut-off voltage are 4.5V and 3.0V respectively, and the battery is charged at a rate of 0.1C to the charge cut-off voltage and then discharged to the discharge cut-off voltage. After activation, the test data is obtained by setting a 1C rate cycle for 80 weeks.
[0131] Capacity retention after 50-week 1C cycle at 45℃: After the battery is assembled, it is placed on a battery tester (Xinwei integrated electric cabinet) for electrical performance testing. The test environment is a constant temperature of 45℃, with a charge cut-off voltage of 4.5V and a discharge cut-off voltage of 3.0V. After charging at a rate of 0.1C to the charge cut-off voltage and then discharging to the discharge cut-off voltage, the test data is obtained after activation at a rate of 1C for 50 weeks.
[0132] The performance test is shown in Table 1:
[0133] Table 1
[0134] Group Button half-cell 0.1C discharge capacity (mAh / g) Button half-cell first discharge efficiency (%) Button half-cell 4C discharge capacity retention rate (%) Capacity retention rate of button cell after 80 cycles at room temperature and 1C (%) Button half-cell capacity retention after 50 cycles at 45°C and 1C (%) Example 1 188.7 95.6 97 89 85 Example 2 188.5 95.1 96 88 83 Example 3 188.5 95.0 95 88 83 Example 4 187.2 94.3 87 78 79 Example 5 187.4 94.5 88 79 79 Example 6 186.3 94.2 88 83 80 Example 7 186.9 94.9 87 80 80 Example 8 186.5 94.4 88 77 75 Example 9 188.6 95.4 97 86 83 Example 10 188.2 95.3 96 87 84 Embodiment 11 187.1 94.8 95 85 83 Example 12 187.9 94.9 94 85 82 Embodiment 13 187.3 94.5 94 84 79 Embodiment 14 187.5 94.8 93 83 80 Embodiment 15 187.5 94.2 92 85 80 Example 16 187.6 94.1 92 86 80 Embodiment 17 185.3 94.8 95 86 81 Embodiment 18 183.2 82.0 73 65 61 Embodiment 19 182.5 83.0 74 66 60 Embodiment 20 181.0 82.7 75 69 63 Embodiment 21 184.6 86.9 80 73 65 Embodiment 22 180.3 89.2 80 71 60 Embodiment 23 182.4 90.8 82 74 62 Comparative Example 1 180.4 80.6 71 60 54 Comparative Example 2 184.2 86.7 77 68 66 Comparative Example 3 184.6 88.0 78 68 65 Comparative Example 4 183.0 82.1 73 65 61
[0135] Conclusion analysis:
[0136] 1. Through Example 1, Examples 4-5, and Comparative Example 2, the performance tests are shown in Table 2:
[0137] Table 2
[0138] Group Button half-cell 0.1C discharge capacity (mAh / g) Button half-cell first discharge efficiency (%) Button half-cell 4C discharge capacity retention rate (%) Capacity retention rate of button cell after 80 cycles at room temperature and 1C (%) Button half-cell capacity retention after 50 cycles at 45°C and 1C (%) Example 1 188.7 95.6 97 89 85 Example 4 187.2 94.3 87 78 79 Example 5 187.4 94.5 88 79 79 Comparative Example 2 182.7 84.7 73 65 62
[0139] It can be seen from the data in Table 2 that compared with the compound of Comparative Example 2 which does not contain the R2 group, when the R2 group in the compound is changed, the Br group has a much greater effect on improving the performance of the lithium cobalt oxide positive electrode material than the F group and the Cl group. This is because the F group and the Cl group will greatly reduce the activity of the delocalized π bond on the benzene ring, reduce the stability of the benzene ring, and thus affect the performance of the positive electrode material.
[0140] 2. Through Example 1, Examples 6-8, and Comparative Example 3, the performance tests are shown in Table 3:
[0141] Table 3
[0142] Group Button half-cell 0.1C discharge capacity (mAh / g) Button half-cell first discharge efficiency (%) Button half-cell 4C discharge capacity retention rate (%) Capacity retention rate of button cell after 80 cycles at room temperature and 1C (%) Button half-cell capacity retention after 50 cycles at 45°C and 1C (%) Example 1 188.7 95.6 97 89 85 Example 6 186.3 94.2 88 83 80 Example 7 186.9 94.9 87 80 80 Example 8 186.5 94.4 88 77 75 Comparative Example 3 183.3 83.9 70 63 59
[0143] It can be seen from the data in Table 3 that, compared with the compound mixture without alkyl groups in Comparative Example 3, when the R1 group in the compound is changed, the isopropyl group has a much greater effect on improving the performance of the positive electrode material than other alkyl groups. This is because if an alkyl group with a smaller carbon chain number is used to replace the isopropyl group, the activity of the benzene ring will decrease; and if an alkyl group with a larger carbon chain number is used to replace the isopropyl group, the steric hindrance is relatively large, which affects the coating effect of onium chloride on the surface of lithium cobalt oxide, thereby affecting the electrochemical performance of the positive electrode material.
[0144] 3. Through Example 1, Example 9-10, Example 22-23, the performance test is shown in Table 4:
[0145] Table 4
[0146] Group Button half-cell 0.1C discharge capacity (mAh / g) Button half-cell first discharge efficiency (%) Button half-cell 4C discharge capacity retention rate (%) Capacity retention rate of button cell after 80 cycles at room temperature and 1C (%) Button half-cell capacity retention after 50 cycles at 45°C and 1C (%) Example 1 188.7 95.6 97 89 85 Example 9 188.6 95.4 97 86 83 Example 10 188.2 95.3 96 87 84 Embodiment 22 180.3 89.2 80 71 60 Embodiment 23 182.4 90.8 82 74 62
[0147] It can be seen from the data in Table 4 that, compared with Example 22 in which no metal compound containing element D is added, doping with Al2O3, TiO2, and MgO has a good effect on improving the performance of the positive electrode material. However, when zirconium oxide is used, the performance of the obtained positive electrode material is only slightly improved compared with that of Example 22. This is because after zirconium oxide is used to replace magnesium oxide, the former has a certain melting effect, which will accelerate the fusion between the primary particles of lithium cobalt oxide, resulting in an increase in the degree of fusion and an increase in the particle size, thereby extending the lithium ion diffusion path and reducing the rate performance; on the other hand, in the solid phase synthesis of zirconium oxide, a part of the cations form Zr 4+ Ions, because the radius of the ions is relatively close to that of lithium ions, lithium ion replacement will occur. This replacement can easily cause distortion of the internal structure of the material and affect the diffusion stability of lithium ions during the cycle. At the same time, the loss of lithium in the structure will further lead to a decrease in the capacity performance of the material. It can be seen that not all metal oxides can achieve this effect.
[0148] 4. It can be seen from Example 1 and Examples 2-3, and Examples 11-14 that, combined with the data in Table 1, during the preparation process, when the mass ratio of the raw materials lithium source, cobalt source and metal oxide of element D, the addition amount of the coating and the metal oxide of element D, and the sintering process of the primary sintered body and the secondary sintered body are changed to a certain extent, the performance of the positive electrode material obtained is close.
[0149] 5. The performance tests of Example 1, Examples 15-16, and Examples 18-19 are shown in Table 5:
[0150] Table 5
[0151] Group Button half-cell 0.1C discharge capacity (mAh / g) Button half-cell first discharge efficiency (%) Button half-cell 4C discharge capacity retention rate (%) Capacity retention rate of button cell after 80 cycles at room temperature and 1C (%) Button half-cell capacity retention after 50 cycles at 45°C and 1C (%) Example 1 188.7 95.6 97 89 85 Embodiment 15 187.5 94.2 92 85 80 Example 16 187.6 94.1 92 86 80 Embodiment 18 183.2 82 73 65 61 Embodiment 19 182.5 83 74 66 60
[0152] It can be seen from the data in Table 5 that when the insulation temperature in step 4 is lower than 80°C, the compound cannot be complexed with the coating E, resulting in poor performance of the positive electrode material; similarly, when the insulation temperature in step 4 is higher than 110°C, the compound on the surface of the positive electrode material will be decomposed during the coating process, resulting in poor coating effect, which in turn leads to poor performance of the positive electrode material.
[0153] 6. Through Example 1, Example 17 and Examples 20-21, the performance tests are shown in Table 6:
[0154] Table 6
[0155] Group Button half-cell 0.1C discharge capacity (mAh / g) Button half-cell first discharge efficiency (%) Button half-cell 4C discharge capacity retention rate (%) Capacity retention rate of button cell after 80 cycles at room temperature and 1C (%) Button half-cell capacity retention after 50 cycles at 45°C and 1C (%) Example 1 188.7 95.6 97 89 85 Embodiment 17 185.3 94.8 95 86 81 Embodiment 20 181.0 82.7 75 69 63 Embodiment 21 184.6 86.9 80 73 65
[0156] It can be seen from the data in Table 6 that, compared with the positive electrode material obtained in Example 20 without adding the coating E, when Co(OH)2 or CoOOH is used for coating, the performance improvement effects brought by the two are similar; however, when other coatings such as cobalt iodide are selected, the same effect cannot be achieved. This is because Co(OH)2 or CoOOH can more easily form a uniform coating on the material and improve the consistency of the surface state of the material, while the use of other cobalt-containing compounds may result in uneven coating or produce toxic groups after thermal decomposition, which may easily lead to a decrease in the capacity, rate and high temperature resistance of the material. It can be seen that the coating Co(OH)2 or CoOOH is irreplaceable.
[0157] 7. Through Example 1 and Comparative Examples 1-7, the performance tests are shown in Table 7:
[0158] Table 7
[0159] Group Button half-cell 0.1C discharge capacity (mAh / g) Button half-cell first discharge efficiency (%) Button half-cell 4C discharge capacity retention rate (%) Capacity retention rate of button cell after 80 cycles at room temperature and 1C (%) Button half-cell capacity retention after 50 cycles at 45°C and 1C (%) Example 1 188.7 95.6 97 89 85 Comparative Example 1 180.4 80.6 71 60 54 Comparative Example 2 184.2 86.7 77 68 66 Comparative Example 3 184.6 88.0 78 68 65 Comparative Example 4 183.0 82.1 73 65 61
[0160] Compared with Comparative Example 1 without using the compound, the performance of the positive electrode material is significantly improved after using the compound in Example 1.
[0161] Then, comparative examples 2-3 were observed. Compared with example 1, the compounds 1 and 2 used for coating lacked the bromine group and isopropyl group, respectively. Meanwhile, comparative example 4 was observed. Compared with example 1, the compounds used for coating were a mixture of compounds containing at least one of a benzene ring, an isopropyl group, a bromine group and an onium group, respectively, and the molar ratio of the benzene ring, isopropyl group, bromine group and onium group and the total addition amount were the same as those in example 1.
[0162] When the above two cases are used for coating, although the performance of the positive electrode material can be improved, it is far less than the performance improvement effect of the compound. It can be seen that the benzene ring, isopropyl group, bromine group and onium group must be on the same compound to bring about the improvement effect in Example 1, and there is a synergistic effect between the four, which can further improve the electrochemical performance of the positive electrode material.
[0163] The above embodiments are preferred implementation modes of the present application, but the implementation modes of the present application are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principles of the present application shall be equivalent replacement methods and shall be included in the protection scope of the present application.
Claims
1. The compound is used as a coating agent for lithium cobalt oxide positive electrode materials, characterized in that: The general structural formula of the compound is shown in Formula I: Formula I; Where R1 is C 1-4 alkyl; R2 is halogen.
2. The use according to claim 1, characterized in that The R1 is at least one of methyl, ethyl, n-propyl, isopropyl, n-butyl and isobutyl; The halogen is at least one of fluorine, chlorine, bromine and iodine.
3. The use according to claim 1, characterized in that The R1 is isopropyl, and the halogen is bromine.
4. The use according to claim 1, characterized in that The preparation method of the compound specifically comprises the following steps: Step A: Add compound A, n-propanol, 40% glyoxal aqueous solution, and deionized water into a reaction kettle, and slowly add a pH adjuster at a speed of 300 r / min, stir for 1 to 3 hours, then add 170 to 210 ml of deionized water, filter, wash with alcohol, and dry to obtain compound B; Step B: prepare a 4 mol / L hydrogen chloride dioxane solution, add it together with paraformaldehyde into a reaction kettle, stir at 300 r / min for 25 to 45 min, add compound B and tetrahydrofuran, stir for another 1.8 to 2.2 h, and filter under reduced pressure to obtain a solid powder; Step C: dissolving the solid powder in dichloromethane, adding ether for precipitation, and filtering to obtain the compound; The general structural formulas of compound A and compound B are shown in formula II and formula III: Formula II; Formula III.
5. The use according to claim 4, characterized in that In the step A, the molar ratio of compound A, n-propanol, glyoxal, pH regulator and water is 1:100-112:0.9-1.2:0.05-0.07:40-50; In the step B, the molar ratio of paraformaldehyde, hydrogen chloride, compound B and tetrahydrofuran is 1:1.15-1.20:0.39-0.46:9-11; In the step C, the mass ratio of dichloromethane to solid powder is 6.61-13.2:1, and the mass ratio of ether to solid powder is 18.4-22.1:
1.
6. A lithium cobalt oxide positive electrode material, characterized in that: It comprises a lithium cobalt oxide core layer and a compound coated on the surface of the lithium cobalt oxide core layer, and the general structural formula of the compound is shown in Formula I: Formula I; Where R1 is C 1-4 alkyl; R2 is halogen.
7. A method for preparing the lithium cobalt oxide positive electrode material according to claim 6, characterized in that: The compound is coated on the surface of the lithium cobalt oxide core layer.
8. The method for preparing a lithium cobalt oxide positive electrode material according to claim 7, characterized in that: The following steps are involved: Step 1: Mixing and sintering a lithium source and a cobalt source to prepare a sintered material; Step 2: Mix the compound and the calcined material and heat and keep the mixture warm to obtain a lithium cobalt oxide positive electrode material.
9. The method for preparing a lithium cobalt oxide positive electrode material according to claim 7, characterized in that: The specific steps include: Step 1: Mixing a cobalt source, a lithium source, and a metal oxide containing element D to obtain a mixed material; Step 2: placing the mixed material in an air atmosphere, and performing one-time sintering, jaw crushing, rolling, crushing, screening and demagnetization operations to obtain a primary sintered material; Step 3: Mix the primary sintered material with the coating E and the metal oxide containing the element D, place in an air atmosphere for secondary sintering, crushing, sieving, and demagnetization to obtain a secondary sintered material; Step 4: After mixing the secondary sintered material with the compound, heating and maintaining the temperature, a lithium cobalt oxide positive electrode material is obtained.
10. The method for preparing a lithium cobalt oxide positive electrode material according to claim 9, characterized in that: The element D is selected from at least one of Mg, Al and Ti: The coating E is selected from at least one of Co(OH)2 and CoOOH; In step 3, the amount of coating E added is 1-2% of the mass of the primary sintering material, and the amount of metal oxide containing element D added is 0.1-0.3% of the mass of the primary sintering material; The added amount of the compound in step 4 is 0.06% to 0.16% of the mass of the secondary sintered body.
11. A lithium cobalt oxide battery, characterized in that: Contains the lithium cobalt oxide positive electrode material according to claim 6.
Citation Information
Patent Citations
Lithium battery electrode plate and preparation method thereof
CN109560254A
Composite lithium-rich material, preparation method thereof, positive electrode and secondary battery
CN116598501A
Catalysts for polymerizing cyclic olefin
CN101282982A